Efeitos da imersão em água fria no desempenho subsequente de atividades intermitentes de alta intensidade - SANTOS, Elton de Almeida dos (2019)
Cryotherapy is widely used as a therapeutic mechanism in individuals practicing intense activities, its properties help in the recovery of muscle damage. The aim of this study was to identify the subsequent effects of cold water immersion on physical performance markers. Two sessions of the anaerobic resistance protocol (RAST) with a 10-minute interval were applied to verify the effects on heart rate, vertical jump, lower limb power and subjective perception of effort. Nine male futsal athletes were divided into two groups : With cooling (ICE) using cold water immersion at hip height for 10 minutes at a temperature of 12Cº ~ 15Cº; while the group without cooling (CONTROL) with 10 minutes of active rest (walking), where there was no cooling. The variables were collected at rest and after each RAST, in the ICE and CONTROL groups. The results showed that there was a decrease in power in the ICE group in which there were differences between the GELO_PRÉ and GELO_PÓS conditions (p = 0.02), between Sprints (p = 0.001), but without interaction between condition and sprint ( p = 0.22), already in the heart rate, vertical jump and subjective perception of effort did not show significant differences between the ICE / CONTROL conditions. It is concluded that the application of immersion cooling does not favor the subsequent performance of intermittent high intensity activity.